PERCEPTION OF ADULTS (25 YEARS OLD AND ABOVE) ABOUT PENIS SIZE AND SEXUAL SATISFACTION IN NIGERIA: A CROSS-SECTIONAL STUDY - Akinduyo, Tosin Emmanuel; Mabaso, N P M (Mandala Of Health, 2024)
Background: The perception of adults about penis size and sexual satisfaction is crucial to enjoying all sorts of sexual relationships or intimacy. However, communication about how penis size influences sexual satisfaction has been consciously kept under the lid, leading to a series of worries such as prostitution, sexual deviations, infidelity, nagging, domestic violence and suicidal ideations. Aim: The study investigated the perception of adults (25 years and above) about penis size and sexual satisfaction. Also, the authors examined the perception of adults’ marital status and gender about penis size and sexual satisfaction. Methods: Using a descriptive survey research design, data were gathered from 221 respondents who were 25 years old and above. A simple random sampling technique was used to select adults for the study. The self-developed research instrument tagged “ PSSSQ” was used for data collection. The validity and reliability (r=0.68) of the research instrument were ensured by the researchers. Results: The findings revealed that moderate penis size is chiefly preferred for sexual satisfaction by adults. Conclusion: Given any penis size to get sexual satisfaction, each male or female involved in any sexual relationship, should mutually commit to the effective usage of any penis size that can enhance sexual gratification.